Effects adverse of treatment with selective inhibitors of serotonin recaptation on the fetus and neonatals of mothers with gestational depression: A critical review (Research, Society and Development, 2021)
Depression is one of the most common psychiatric disorders, due to the high incidence in this decade, a greater predominance of occurrence in women, among them the major depressive disorder in pregnancy. When the diagnosis is made, the treatment is according to the level of the disease, when it comes to a moderate to severe level, pharmacological treatment with antidepressants begins. Among them, the most prescribed are selective serotonin reuptake inhibitors (SSRIs), they have become first-line drugs of choice because they have a higher safety than the others. However, treatment with SSRIs during pregnancy has implicated several undesirable effects in fetuses and neonates. Therefore, the objective of this study was to investigate the adverse effects on the fetus / neonates of depressive women who underwent drug therapy with SSRIs. This study was characterized in a critical review, using the databases of Pubmed/MEDLINE, Scopus and Web of Science, in which 35 articles were included. After careful analysis of the studies, it was found that SSRI therapy in gestational depression increases the risks to the fetus and neonates for birth defects, such as: cardiac malformation, neonatal abstinence, persistent pulmonary hypertension and possible association with autism spectrum disorder. Therefore, based on scientific evidence, the SSRI drug protocol generates harmful effects on the child, however, the use of antidepressants during pregnancy is often inevitable. Thus, in cases where it may be necessary to use SSRIs, a decision on such a therapeutic approach should be evaluated by analyzing the risks of untreated depression and the risk / benefit ratio of the use of medications.